Background rates of adverse events of special interest for COVID-19 vaccine safety monitoring in the United States, 2019–2020. Issue 2 (9th January 2023) - Moll, Keran; Lufkin, Bradley; Fingar, Kathryn R.; Ke Zhou, Cindy; Tworkoski, Ellen; Shi, Chianti; Hobbi, Shayan; Hu, Mao; Sheng, Minya; McCarty, Jillian; Shangguan, Shanlai; Burrell, Timothy; et al.
Highlights: Assessed background incidence rate of 17 AESI in 6 administrative claims databases. Background rates varied by database and demographic characteristics. Rates of most AESI increased with age and were higher among males. AMI (Medicare) and anaphylaxis (all databases) rates showed seasonality. AESI rates fluctuated in 2020, but most returned to 2019 levels after May 2020. Abstract: Background: The U.S. Food and Drug Administration (FDA) Biologics Effectiveness and Safety (BEST) Initiative conducts active surveillance of adverse events of special interest (AESI) after COVID-19 vaccination. Historical incidence rates (IRs) of AESI are comparators to evaluate safety. Methods: We estimated IRs of 17 AESI in six administrative claims databases from January 1, 2019, to December 11, 2020: Medicare claims for adults ≥ 65 years and commercial claims (Blue Health Intelligence®, CVS Health, HealthCore Integrated Research Database, IBM® MarketScan® Commercial Database, Optum pre-adjudicated claims) for adults < 65 years. IRs were estimated by sex, age, race/ethnicity (Medicare), and nursing home residency (Medicare) in 2019 and for specific periods in 2020. Results: The study included >100 million enrollees annually. In 2019, rates of most AESI increased with age. However, compared with commercially insured adults, Medicare enrollees had lower IRs of anaphylaxis (11 vs 12–19 per 100, 000 person-years), appendicitis (80 vs 117–155), and narcolepsy (38 vs 41–53). Rates were higher in males than females for most AESI across databases and varied by race/ethnicity and nursing home status (Medicare). Acute myocardial infarction (Medicare) and anaphylaxis (all databases) IRs varied by season. IRs of most AESI were lower during March–May 2020 compared with March–May 2019 but returned to pre-pandemic levels after May 2020. However, rates of Bell's palsy, Guillain-Barré syndrome, narcolepsy, and hemorrhagic/non-hemorrhagic stroke remained lower in multiple databases after May 2020, whereas some AESI (e.g., disseminated intravascular coagulation) exhibited higher rates after May 2020 compared with 2019. Conclusion: AESI background rates varied by database and demographics and fluctuated in March–December 2020, but most returned to pre-pandemic levels after May 2020. It is critical to standardize demographics and consider seasonal and other trends when comparing historical rates with post-vaccination AESI rates in the same database to evaluate COVID-19 vaccine safety.